Relationships Between Burnout and Role Ambiguity, Role Conflict and Employee Absenteeism Among Health Workers [Burnout y Su Relación Con la Ambigüedad de Rol, Conflicto de Rol y Absentismo Laboral en Trabajadores de la Salud] - Mena-Miranda, L; Olivares-Faundez, V (Sociedad Chilena de Psicologia Clinica, 2014)
The aim of this research was to analyze the influence of some psychosocial risk factors in the development of burnout and to analyze the influence of this phenomenon on employee absenteeism. The study sample included 142 health care workers. The data analysis included descriptive statistics and multiple linear regression models. The results confirmed the influence of role ambiguity and role conflict on burnout [F (2.139) = 26.720; p < .001], but the influence of burnout on employee absenteeism was not confirmed. However, a significant and positive relationship has been shown between burnout and employee absenteeism (? = 0.197; p < .05). In conclusion, the findings of this study support the claims that role conflict is a more intense predictor of the emotional component of burnout (burnout; ? = 0.585; p < .001). Additionally, there is evidence that prolonged emotional strain could encourage employee absenteeism. © 2014 by Sociedad Chilena de Psicología Clínica.